Implementation of AES algorithm into information investigation autopsy (IIA) / Ahmad Wafiy Hamad Zaki - Hamad Zaki, Ahmad Wafiy Hamad Zaki (2013)
Information Investigation Autopsy (IIA) is the tools that can captured the information needed on the Local Area Network environment and later needed to be secured, the IIA need a module that can to secure the evidence captured from any harm. The objectives of this project are to apply the encryption algorithm into these tools for securing the information collected by keystroke logging mechanism. Therefore the Advance Encryption Standard (AES) algorithm is being implemented to secure the evidence captured. AES use high level description of algorithm that based on a design formula as a substitution permutation and fast implementation on software. AES also have 128 bits fixed on block size with the key size of 256, 192, or 128 bits and operates on 4 times 4 column byte matrix. The result of this project later will benefit the user.